Genome-Wide Identification and Expression Analysis of MYB Transcription Factor Superfamily in Dendrobium catenatum - Zhang, Tingting; Cui, Zheng; Li, Yuxin; Kang, Yuqian; Song, Xiqiang; Wang, Jian; Zhou, Yang (Frontiers in Genetics, 2021)
Dendrobium catenatum is an important traditional Chinese medicine and naturally grows on tree trunks and cliffs, where it can encounter diverse environmental stimuli. MYB transcription factors are widely involved in response to abiotic stresses. However, the MYB gene family has not yet been systematically catalogued in D. catenatum. In this study, a total of 133 MYB proteins were identified in D. catenatum, including 32 MYB-related, 99 R2R3-MYB, 1 3R-MYB, and 1 4R-MYB proteins. Phylogenetic relationships, conserved motifs, gene structures, and expression profiles in response to abiotic stresses were then analyzed. Phylogenetic analysis revealed MYB proteins in D. catenatum could be divided into 14 subgroups, which was supported by the conserved motif compositions and gene structures. Differential DcMYB gene expression and specific responses were analyzed under drought, heat, cold, and salt stresses using RNA-seq and validated by qRT-PCR. Forty-two MYB genes were differentially screened following exposure to abiotic stresses. Five, 12, 11, and 14 genes were specifically expressed in response to drought, heat, cold, and salt stress, respectively. This study identified candidate MYB genes with possible roles in abiotic tolerance and established a theoretical foundation for molecular breeding of D. catenatum.